Synthesis of Cu 2 SnSe 3 nanocrystals for solution processable photovoltaic cells - Batabyal, Sudip Kumar (2013)
This paper describes the synthesis of ternary chalcogenide Cu2SnSe3 nanocrystals as an alternative solar absorber material to conventional quaternary CuInxGa1–xSe2. We used the hot coordination solvent method with hexadecylamine as the capping ligand for the first time for this material system. Using a variety of characterization techniques, such as X-ray diffraction, selected area electron diffraction, convergent beam electron diffraction, and Raman spectroscopy, the nanocrystals were found to be monoclinic Cu2SnSe3 with an optical energy band gap of 1.3 eV and have a narrow size distribution. These nanocrystals are shown to be photosensitive in the range of wavelengths corresponding to the solar spectrum, which makes them highly promising as alternative photon absorber materials for photovoltaic applications.